Proctor-guided virtual reality–enhanced three-dimensional video-assisted thoracic surgery: an excellent tutoring model for lung segmentectomy. Issue 6 (December 2021) - Guerrera, Francesco; Nicosia, Samanta; Costardi, Lorena; Lyberis, Paraskevas; Femia, Federico; Filosso, Pier Luigi; Arezzo, Alberto; Ruffini, Enrico
Objective: Lung segmentectomy using video-assisted thoracoscopic surgery (VATS) is an effective strategy to treat early-stage lung cancer. The objective of this case report is to show the efficacy of Hyper Accuracy 3D™ (HA3D) reconstruction as a tool for trainee surgeons and expert surgeons to perform complex procedures. Methods: An 84-year-old man was treated for colon-rectal cancer. During follow-up, a pulmonary nodule on the right anterior upper lobe suspected for intestinal metastasis was revealed by a computed tomography scan. According to functional tests and radiology, a right anterior upper lobe segmentectomy was planned. HA3D lung reconstruction was used during surgery. Results: Using the HA3D virtual model, the procedure was performed with healthy tissue sparing, ensuring safe resection margins. No postoperative morbidities were noted. The patient referred good pain control. The hospital stay was 6 days. Conclusions: VATS segmentectomy is a technically demanding procedure. HA3D lung reconstruction can help surgeons effectively perform the resection, aiding at individuating intersegmental planes, bronchi, and vessels, guaranteeing oncologic radicality and safe surgical margins, and preserving respiratory function.